Impact of co-feeding cracked light products on visbreaking of vacuum residue deasphalted oil. (15th February 2022) - Tannous, Joy H.; Yan, Yuwei; De Klerk, Arno
Highlights: Thermal alkylation of binuclear aromatics was a source of n -pentane insoluble asphaltenes. Co-feeding light cracked material did not cause observable change in progression of visbreaking. Evidence for suppression of n -pentane insolubles by co-feeding light material was inconclusive. Abstract: The impact of co-feeding light cracked products on thermal conversion was investigated due to reports that indicated suppression of coking and other benefits during such operation. Specific attention was paid to n -pentane insoluble asphaltenes content and formation. In this study all reactions were performed at 400 °C and 2 MPa initial nitrogen pressure, using a vacuum residue deasphalted oil obtained from Canadian oilsands bitumen. The impact of co-feeding distilled cracked naphtha and kerosene at 5 to 15 wt% was studied. Control reactions included self-reactions of all materials and reactions where the vacuum residue deasphalted oil was replaced by naphthalene. The presence of the distilled cracked naphtha and kerosene did not cause an observable change in the progression of the thermal reaction and no conclusive evidence was found that the development of n -pentane insoluble material in the products was reduced. The reactions products showed no relationship between n -pentane insoluble content, vacuum residue conversion and free radical content. In control experiments the conversion of distilled cracked naphtha and kerosene in naphthalene caused the formation on n -pentane insoluble material, which was not observed during self-reaction of these materials. The results suggested that some of the naphthalene was directly thermally alkylated at 400 °C and that at least some of the resulting products became n -pentane insoluble.